Collaborative Management Model in the Implementation of Indonesian’s Makan Bergizi Gratis (MBG) Program in Schools - Abdul Canter Sangaji; R. Madhakomala; Abdul Canter Sangaji; Dhioatmaja Megafajari; Dhioatmaja Megafajari (Universitas Negeri Malang, 2026)
Makan Bergizi Gratis (MBG) is a strategic government policy aimed at improving students' nutritional status in Indonesia. This study analyzes the collaborative management model applied in the implementation of MBG in Duren Sawit District, East Jakarta, Indonesia. A qualitative case study approach was employed, with data collected through in-depth interviews with three purposively selected informants representing the district, operational, and school tiers of MBG governance, supplemented by document analysis and policy review. Data were analyzed using the Miles, Huberman, and Saldana interactive model. The findings reveal that MBG implementation in Duren Sawit has formed a collaborative governance pattern involving the district education office, SPPG, schools, community health centers, security agencies, and the environmental agency within a single cross-sector coordination forum. From the SPPG perspective, coordination encompasses data validation, organoleptic food testing, rapid-response reporting mechanisms, and multi-party crisis management. However, several critical challenges were identified: the absence of a uniform national SOP for district-level coordination, legal and hygiene gaps in catering kitchens (only 13 of 44 kitchens held hygiene certificates), unresolved waste-management integration, and the lack of a structured evaluation system. Measurable positive outcomes include an increase in first-grade students' average body weight from 25-30 kg to 33 kg after program implementation. This study proposes the Collaborative School Feeding Governance (CSFG) model, comprising five dimensions, cross-sector coordination, operational collaboration, food-quality supervision, community participation, and adaptive evaluation, as a replicable framework for effective and sustainable school feeding governance.